Differences in kinematics of the support limb depends on specific movement tasks of take-off - Vladimír Hojka; Radka Bačáková; Petr Kubový (Palacký University Olomouc, 2016)
Background: Many sport activities are a sequence of jumps (running, jumping, hurdling etc.). Each jump flight phase is the result of the execution of the previous support phase. Objective: The goal of the research was to identify differences in adjustment of the support lower limb and differences in take-off kinematics in specific take-off movement task. Methods: 14 male athletes (22.6 ± 4.4 years; 182.4 ± 5.3 cm; 74.7 ± 6.2 kg) took part in a laboratory experiment. Each athlete performed five different take-off movements (running, acceleration running - second step, long jump take-off, high jump take-off and take-off to the hurdle). System Qualisys was used to analyze the kinematics of the support limb. Dynamics of the support phase was monitored via force plate. ANOVA and Bonferroni post-hoc test were used to measure the significance of the differences between different take off tasks. Results: Dynamic characteristic showed significant differences in take-off (p < .001). This variability is caused by differences in kinematic parameters at the instant of touch-down, minimum joint angles and take-off. The most important finding was different variability in range of motion in eccentric or concentric phases of each jump. Vertically orientated jumps are terminated in a higher degree of extension. Horizontal take-off types are characterized by the highest ranges of motion especially in the ankle joint. Conclusions: The support lower limb compliance is adjusted to the required task, which is related to lower limb kinematics during the support phase. High range of motion in each joint refers to more compliant adjustment of the joint.